TECHNICAL SECURITY SYSTEMS - DESIGN COURSE, IMPLEMENTATION, SUITABILITY OF CONTENTS - MARSZAŁEK, Aleksander; BIAŁOGŁOWSKI, Robert; KRUPA, Krzysztof (Trends in education, 2014)
The paper presents selected aspects of designing and implementing content of the "technical security systems." Theoretical considerations supplemented by presentation of test results suitability of the content of education.
Keywords: technical security systems; electronics; teaching.